Analysis of Didactic Engineering on the Fibonacci Generalized Sequence Complexification Model, an approach in an initial teacher training course (Research, Society and Development, 2019)
The educational object is a review of an academic master's dissertation in science and mathematics education of the Federal Institute of Education, Science and Technology of the State of Ceara, bringing the application of two methodologies, being: Didactics, and other teaching - Theory of Didactic Situations. This review is divided into 3 topics: Methodology and the Fibonacci Model, Epistemic-Mathematical Field and Data Collection and Analysis. However, the process of Fibonacci sequence complexification, applied in the initial teacher training course, is carried out through didactic transposition.